“HUA MULAN” IN CHINESE PHILOSOPHY: A STUDY OF THE DISNEY FILM MULAN (2020) - Rudy, Rudy (Asosiasi dosen IDEBAHASA KEPRI, 2024)
One of the popular heroines from a Chinese legend in a movie produced by Disney Film is Hua Mulan which also plays a significant role in inspiring audiences around the world. This qualitative research aims at identifying the images displayed by the main character Hua Mulan in the action movie Mulan (2020) from the Chinese philosophical perspective and explaining the attractiveness of the film from a popular culture perspective. The primary data were gathered through careful observation of the main Chinese heroine character Hua Mulan from film scenes. They were then analyzed by using Barthes’ semiotic theory to conceptualize the depiction of the character from the Chinese philosophical perspective and to relate it to the elements of popular culture. The study revealed that Hua Mulan could signify the value of filial piety and courage, particularly in the perspective of Chinese philosophy. From a popular culture view, the legendary characterization of Hua Mulan was the main attraction to draw audience’s attention, especially those who expected to see the Chinese heroine in a colossal action movie played by popular actors.